Water and chlorine content in the Martian soil along the first 1900 m of the Curiosity rover traverse as estimated by the DAN instrument. Issue 7 (15th July 2014) - Mitrofanov, I. G.; Litvak, M. L.; Sanin, A. B.; Starr, R. D.; Lisov, D. I.; Kuzmin, R. O.; Behar, A.; Boynton, W. V.; Hardgrove, C.; Harshman, K.; Jun, I.; Milliken, R. E.; et al.
Abstract The presence of hydrated phases in the soil and near‐surface bedrock of Gale Crater is thought to be direct evidence for water‐rock interaction in the crater in the ancient past. Layered sediments over the Gale Crater floor are thought to have formed in past epochs due to sediment transport, accumulation, and cementation through interaction with fluids, and the observed strata of water‐bearing minerals record the history of these episodes. The first data analysis of the Dynamic Albedo of Neutrons (DAN) investigation on board the Curiosity rover is presented for 154 individual points of active mode measurements along 1900 m of the traverse over the first 361 Martian solar days in Gale crater. It is found that a model of constant water content within subsurface should be rejected for practically all tested points, whereas a two‐layer model with different water contents in each layer is supported by the data. A so‐called direct two‐layer model (water content increasing with depth) yields acceptable fits for odometry ranges between 0 and 455 m and beyond 638 m. The mean water (H2O) abundances of the top and bottom layers vary from 1.5 to 1.7 wt % and from 2.2 to 3.3 wt %, respectively, while at some tested spots the water content is estimated to be as high as 5 wt %. The data for odometry range 455–638 m support an inverse two‐layer model (water content decreasing with depth), with an estimated mean water abundance of 2.1 ± 0.1 wt % and 1.4 ± 0.04 wt % in the top and bottom layers, respectively.